Strategies for Social Change - Maney, Gregory M. (Book collections on Project MUSE., 2012)
The theory and practice of social movements come together in strategy-whether, why, and how people can realize their visions of another world by acting together. Strategies for Social Change offers a concise definition of strategy and a framework for differentiating between strategies. Specific chapters address microlevel decision-making processes and creativity, coalition building in Northern Ireland, nonviolent strategies for challenging repressive regimes, identity politics, GLBT rights, the Christian right in Canada and the United States, land struggles in Brazil and India, movement-media.